2021
DOI: 10.1016/j.apnu.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Covid-19 on sleep quality, anxiety and depression on healthcare staff at a tertiary hospital in Turkey

Abstract: Background:The Covid-19 pandemic has forced healthcare staff into an unprecedented situation, such as making tough decisions and practising under enormous pressure. Aim: This study was designed to investigate the effect of Covid-19 on sleep quality, anxiety and depression in healthcare staff at a tertiary hospital. Methods: This descriptive and cross-sectional study recruited healthcare staff working at a tertiary hospital. Those who had given their informed consent participated in this study between April 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…Zhao et al (2020) found that HCWs who experience psychological stress and long working hours will have poor sleep quality. This is supported by Yigitoglu et al (2021), who found that the workload of HCWs, such as caring for and educating patients, can hurt the quality of their sleep. Recent research) stated that an increase in job stress scores would have implications for their poor sleep quality scores (Deng et al, 2020).…”
Section: Hypotheses Developmentmentioning
confidence: 87%
See 2 more Smart Citations
“…Zhao et al (2020) found that HCWs who experience psychological stress and long working hours will have poor sleep quality. This is supported by Yigitoglu et al (2021), who found that the workload of HCWs, such as caring for and educating patients, can hurt the quality of their sleep. Recent research) stated that an increase in job stress scores would have implications for their poor sleep quality scores (Deng et al, 2020).…”
Section: Hypotheses Developmentmentioning
confidence: 87%
“…The sleep quality dimension covers sleep efficiency, latency, duration, waking after falling asleep, and sleep disturbances. Yigitoglu et al (2021), conducted a qualitative study on HCWs during the pandemic. They found that the poor quality of sleep experienced by HCWs was associated with the level of depression they experienced.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor sleeping pattern can be associated with increased symptoms of anxiety and stress during the Covid‐19 pandemic (Saraswathi et al, 2020 ). Individuals' negative thoughts about the contagion of the disease to themselves or their family members and the unhygienic environment have been reported as sources of intense anxiety (Tasdemir Yigitoglu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals' negative thoughts about the contagion of the disease to themselves or their family members and the unhygienic environment have been reported as sources of intense anxiety (Tasdemir Yigitoglu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%